Modeling principles, criteria and indicators to assess water sector governance for climate compatibility and sustainability - Iqbal, Kanwar Muhammad Javed; Khan, Muhammad Irfan; Mikhaylov, Alexey; Shah, Ashfaq Ahmad; Yadykin, Vladimir; Leal Filho, Walter; Tariq, Muhammad Atiq Ur Rehman; Ullah, Wahid (Frontiers in Environmental Science, 2023)
The United Nations SDGs Report 2020 highlighted that about 39 million people were severe climate victims during 2018, while 2019 was the second warmest year on historical record. A 3.2°C increase is anticipated rise in global temperature by the year 2100, whereas the annual global emissions reduction target is lagging behind by about 7.6% for limiting the warming effect to 1.5°. Climatic variations will likely continue with similar trends. Environmental security agenda under SDG-13 requires an integrated climate compatible development (CCD) approach of ‘triple-win strategies’ with inclusive governance mechanism. Existing climate governance arrangements in developing countries are quite complex and lack ownership. In this backdrop, a multivariate mix-method model, that was formulated as an outcome of a study, aimed to assess the adequacy of the overall state of sectoral governance for CCD by combining rules-based and rights-based approaches. This model integrates six governance components, MCDA, SMART, Ratio Scale, and six novel principles of climate governance with a set of sectoral Indicators of 09 CCD Criteria. It proved well for this water sector case study with a cross-section data of 340 KIIs and 17 FGDs in Pakistan, validated statistically. It can be used for periodic sectoral climate governance assessment for CCD.